전력데이터 분석에서 이상점 추출을 위한 데이터 클러스터링 아키텍처에 관한 연구 - 정세훈; Se Hoon Jung; 신창선; Chang Sun Shin; 조용윤; Young Yun Cho; 박장우; Jang Woo Park; 박명혜; Myung Hye Park; 김영현; Young Hyun Kim; et al. (정보처리학회 논문지 (KTSDE), 2017)
과거에는 전력데이터를 분석하는 기법으로 주로 기계학습의 지도학습 기법을 많이 활용하였고 데이터 마이닝 기법을 통한 패턴 검출을 주로 연구하였다. 그러나 전력데이터의 규모 커지고 실시간 데이터 공급이 가능해진 현재에는 과거의 데이터 분류 및 분석 기법을 통한 데이터 분석 연구는 한계가 존재한다. 이에 본 논문에서는 큰 규모의 전력데이터를 분석할 수 있는 클러스터링 아키텍처를 제안한다. 제안하는 클러스터링 프로세스는 비지도학습기법인 K-means 알고리즘의 문제점을 보완하고 전력데이터 수집과 분석까지의 모든 과정을 자동화할 수 있는 프로세스이다. 총 3 Level로 구분하여 Row Data Level, Clustering Level, User Interface Level로 구분하여 전력데이터를 분류 및 분석한다. 또한 클러스터링의 효율성 향상을 위하여 주성분분석 및 정규분포기반의 최적의 클러스터 수 K값 추출과 이상점으로 분류되는 데이터 감소를 위한 변형된 K-means 알고리즘을 제시한다. In the past, researchers mainly used the supervised learning technique of machine learning to analyze power data and investigated the identification of patterns through the data mining technique. Data analysis research, however, faces its limitations with the old data classification and analysis techniques today when the size of electric power data has increased with the possible real-time provision of data. This study thus set out to propose a clustering architecture to analyze large-sized electric power data. The clustering process proposed in the study supplements the K-means algorithm, an unsupervised learning technique, for its problems and is capable of automating the entire process from the collection of electric power data to their analysis. In the present study, power data were categorized and analyzed in total three levels, which include the row data level, clustering level, and user interface level. In addition, the investigator identified K, the ideal number of clusters, based on principal component analysis and normal distribution and proposed an altered K-means algorithm to reduce data that would be categorized as ideal points in order to increase the efficiency of clustering.